Characterising candidate Fusarium graminearum effectors - Kanja, Claire (2023)
Effectors are small, secreted proteins produced by a pathogen that manipulate the host to aid colonisation. The effector repertoire of plant pathogens is a key determinant of the success of pathogen-host interactions and could mean the difference between a compromised or a successful crop harvest. One notorious pathogen, the fungus Fusarium graminearum is the causal agent of Fusarium head blight (FHB), one of the most destructive diseases threatening wheat production worldwide.